Sperm whales Gulf of Mexico 2011-2013 - FastLoc GPS data-reference-data - Irvine, Ladd M.; Follett, Tomas M.; Winsor, Martha H.; Mate, Bruce R.; Palacios, Daniel M. (Movebank Data Repository, 2020)
Irvine LM, Winsor MH, Follett TM, Mate BR, Palacios DM (2020) An at-sea assessment of Argos location accuracy for three species of large whales, and the effect of deep-diving behavior on location error. Animal Biotelemetry 8:20. doi:10.1186/s40317-020-00207-x : Background: Argos satellite telemetry is used globally to track terrestrial and aquatic megafauna, yet the accuracy of this system has been described empirically only for a limited number of species. We used Argos-linked archival tags with Fastloc GPS deployed on free-ranging sperm (Physeter macrocephalus), blue (Balaenoptera musculus), and fin (B. physalus) whales to derive empirical estimates of Argos location errors for these species, examine possible behavior-related differences, and test the effect of incorporating species-specific error parameters on performance of a commonly used movement model. Results: Argos location errors for blue and fin whale tags were similar and were combined (n = 1712 locations) for comparison against sperm whale tags (n = 1206 locations). Location error magnitudes for tags attached to sperm whales were significantly larger than blue/fin whale tags for almost all Argos location classes (LC), ranging from 964 m versus 647 m for LC 3, respectively, to 10,569 m versus 5589 m for LC B, respectively. However, these differences were not seen while tags floated at the surface after release. Sperm whale tags were significantly colder than ambient temperature when surfacing from a dive, compared to blue/fin whale tags (16.9 °C versus 1.3 °C, respectively) leading to larger changes in tag temperature during post-dive intervals. The increased rate of tag temperature change while at the surface was correlated to increased error magnitude for sperm whales but not blue/fin whales. Movement model performance was not significantly improved by incorporating species-specific error parameters. Conclusions: Location accuracy estimates for blue/fin whales were within the range estimated for other marine megafauna, but were higher for sperm whales. Thermal inertia from deep, long-duration dives likely caused transmission frequency drift and greater Argos location error in sperm whales, as tags warmed at the surface during post-dive intervals. Thus, tracks of deep-diving species may be less accurate than for other species. However, differences in calculated error magnitude between species were less than typical scales of movement and had limited effect on movement model performance. Therefore, broad-scale interpretation of Argos tracking data will likely be unaffected, although fine-scale interpretation should be made with more caution for deep-diving species inhabiting warm regions.